2017
DOI: 10.1108/jpif-03-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

UK REITs don’t like Mondays

Abstract: Purpose: The research examines whether REITs returns on the different days of the week differ from each other. Design/methodology/approach: It uses EPRA/NAREIT UK Index daily closing values (GBP) and its two sub-indices FTSE EPRA/NAREIT UK REITs and Non-REITs as dependent variables. It employs Kruskal-Wallis (KW) tests and dummyvariable regression to test the hypothesis. Findings: The overall findings provide evidence that return anomalies exist in the UK REITs. Practical implications: Thought significant, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…Additionally, the day-of-the-week effect was found to be significant, with coefficients for Friday, Thursday, and Monday being positively significant at the conventional level for office, diversified, and industrial REITs, respectively. This finding is consistent with previous research by Jadevicius and Lee (2017), who documented greater returns on Tuesdays than on other days of the week. To further specify the findings of this study, the coefficients for the dummies representing the days of the week were incorporated into the GARCH variance equation, as shown in Table 9.…”
Section: Incorporating the Garch Variance Model Into The Ols Equationsupporting
confidence: 93%
“…Additionally, the day-of-the-week effect was found to be significant, with coefficients for Friday, Thursday, and Monday being positively significant at the conventional level for office, diversified, and industrial REITs, respectively. This finding is consistent with previous research by Jadevicius and Lee (2017), who documented greater returns on Tuesdays than on other days of the week. To further specify the findings of this study, the coefficients for the dummies representing the days of the week were incorporated into the GARCH variance equation, as shown in Table 9.…”
Section: Incorporating the Garch Variance Model Into The Ols Equationsupporting
confidence: 93%
“…Newell et al (2013) investigated the performance of French REITs and concluded that their risk-adjusted returns overperform the stocks over 2003–2012 and are important assets to be included in the mixed-asset portfolio in the post-global financial crisis period. Jadevicious and Lee (1996) investigated the calendar anomalies in the UK market and their results exhibited such anomaly as Hepsen (2012) concluded for the Turkish REIT market.…”
Section: Literature Reviewmentioning
confidence: 87%
“…The increasing popularity of REITs in many major European markets has resulted in a considerable number of empirical studies concentrated on their respective qualitative and quantitative investment characteristics. For example, in Spain (Marzuki and Newell, 2018), Germany (Newell and Marzuki, 2018), the UK (Akinsomi et al, 2018;Jadevicius and Lee, 2017;Newell and Marzuki, 2016), Belgium (Marzuki and Newell, 2019), Turkey (Erol and Tirtiroglu, 2011) and France (Newell et al, 2013 significance of REITs has attracted considerable research interest with a number of studies on Irish REITs scrutinising the crucial role of REITs in the post-GFC recovery, such as their role in stimulating the private rented sector of the Irish housing segment (Duffy et al, 2017) and as an exit mechanism to offload property assets (Mercille and Murphy, 2016). However, an empirical analysis of the investment attributes of Irish REITs is yet to be documented in the literature.…”
Section: Introductionmentioning
confidence: 99%